ASUHAN KEPERAWATAN LANSIA DENGAN PERUBAHAN FUNGSI SISTEM SENSORI PADA PENGLIHATAN DI DESA KATERBAN KABUPATEN PURWOREJO - Mugihartadi, Anti Puspita Sari (Jurnal Ilmiah Keperawatan, 2022)
Background: Aging or an ongoing process of damage to tissue functionality in restoring or maintaining normal structure and function. Vision problems are a common condition in the elderly. The prevalence of elderly with visual impairment in the world is quite high, namely around 285 million people. WHO estimates that the second highest cause of visual impairment in the elderly in the world is cataracts (25.81%). Objective: This study describes nursing care for cataract patients with visual sensory perception disorders. Method: This type of research is a descriptive case study using a nursing process approach that includes assessment, diagnosis, intervention, implementation and evaluation. The subjects in this case study were 2 elderly people with visual sensory perception disorders. Results: Based on the first and second cases after being visited for five days, visual sensory perception improved with increased visual acuity, improved vision and was able to explain cataracts after being given health education and innovative carrot tomato juice. The patient's statements and observations indicate that the patient's sensory perception disorder problem has been resolved. Conclusion: the use of glasses, health education and innovative giving of tomato and carrot juice can help overcome the problem of sensory perception of vision in the elderly. Keywords : Elderly, Sensory Perception, Cataract